A comprehensive review of urban growth studies and predictions using the Sleuth model - Dey, Bratati; Sharma, Poonam (The Scientific Temper, 2024)
Urban growth is a complex phenomenon It has been the subject of in-depth research for the last few years. There are various models used to measure and simulate urban growth. Most of these methods are founded on GIS & RS techniques coupled with the CA algorithm, as only these tools and techniques have the capabilities to conduct spatiotemporal studies, manage spatiotemporal dynamics, and provide a detailed depiction and modeling from the bottom-up tactic. Recently, the slope, land use, exclusion, urbanization, transportation, and hill shade (SLEUTH) model has been the most commonly used model. It is easily accessible because it is open source; moreover, its source code is also easily accessible. The SLEUTH model’s name alludes to the necessary inputs —slope, land use, excluded area, urban extension, transportation, network and hillshade. The model has been used in many cities and has proven to be efficient. The present review paper reviews the past literature pertaining to urban development and prediction to further support the research on urban planning, urban growth and prediction.